Hubungan Burnout Akademik dengan Produktivitas Belajar Mahasiswa Perguruan Tinggi - Dinda Maharani Putri; Rizky Aditya Saputra; Fajar Pratama Nugraha (Gema Cendekia Institute, 2026)
Abstract Academic burnout has become one of the most prevalent psychological issues among university students due to increasing academic demands, achievement pressure, and the complexity of contemporary learning environments. Academic burnout is characterized by emotional exhaustion, cynical attitudes toward academic activities, and reduced academic efficacy, all of which may negatively affect students' learning productivity. This study aims to examine the relationship between academic burnout and learning productivity among university students based on empirical evidence from previous studies. A quantitative approach with a correlational survey design was employed. Data were collected through questionnaires distributed to active university students from various academic disciplines. Pearson correlation and simple linear regression analyses were utilized to examine the relationship between variables. The findings indicate a significant negative relationship between academic burnout and learning productivity. Higher levels of academic burnout are associated with lower levels of learning productivity. These findings support previous studies suggesting that academic burnout reduces learning motivation, academic engagement, academic achievement, and overall learning effectiveness. The study recommends strengthening psychological support services, enhancing academic self-efficacy, and improving student engagement as effective strategies to reduce academic burnout and increase learning productivity in higher education.